Multiculturalism from the Perspective of Islamic Law and Its Application in Education - Yuliani; Syahrul Fadli. R; Yuliarni; Ali Amat; Maigus; Mira Salsabila; Tamrin Kamal; Firdaus (Asian Journal of Applied Education (AJAE), 2026)
This study examines the concept of multiculturalism from the perspectives of classical and contemporary Islamic law and its application in Islamic education. It employs a qualitative, library-based research approach, analyzing academic literature concerning multiculturalism, Islamic law, and Islamic education. The findings indicate that multiculturalism in Islam rests on a strong normative foundation rooted in principles of justice, tolerance, and respect for diversity. From a classical Islamic legal perspective, the multicultural concept is reflected in the Charter of Medina, the *ahl al-dhimmah* concept, and the social practices of early Muslim communities that accommodated plurality. Meanwhile, contemporary Islamic thought offers a reinterpretation of multicultural concepts through approaches emphasizing religious moderation, human rights, and democracy. Multicultural values ​​can be implemented in Islamic education by developing inclusive curricula, strengthening teacher competence, and creating educational environments that value diversity. The study affirms that multicultural education within Islam impacts the cognitive, affective, and psychomotor development of learners, contributing to the creation of an inclusive and harmonious society.